Complete Consistency of the Estimator of Nonparametric Regression Models Based on ρ~-Mixing Sequences. (10th December 2012) - Wang, Xuejun; Xia, Fengxi; Ge, Meimei; Hu, Shuhe; Yang, Wenzhi
Abstract : We study the complete consistency for estimator of nonparametric regression model based on ρ ~ -mixing sequences by using the classical Rosenthal-type inequality and the truncated method. As an application, the complete consistency for the nearest neighbor estimator is obtained.